Local Culture as a Potential of Learning Media for Civic Education: A Study of Civic Values in The Tradition of Pantauan Bunting in Besemah Custom - Rizky Anisa Salsabila; Suyato Suyato (Jurnal Ilmu Pendidikan dan Pembelajaran, 2026)
The Pantauan Bunting tradition is part of a series of traditional wedding customs that not only serve as a social ceremony but are also rich in the values of mutual cooperation, deliberation, responsibility, religiosity, and the strengthening of cultural identity and nationalism. This study aims to examine the civic values embedded in the Pantauan Bunting tradition among the Besemah community in South Sumatra, as well as its relevance as a medium for civic education. This study employs a qualitative approach with a literature review. The results indicate that the values embedded in this tradition align with civic values and can be realized through a contextual approach in education, enabling students to concretely understand civic values through case studies, project-based work, and teacher assessment. The novelty of this study lies in its effort to integrate the Pantauan Bunting tradition as a contextual learning resource that can be utilized in the Civic Education learning process, so that local culture is understood not only as a cultural heritage but also as an educational tool for shaping students’ civic character. This study is limited to an examination of the civic values embodied in the Pantauan Bunting tradition among the Besemah people and its relevance as a teaching tool for Civic Education (PPKn). This study also makes a more specific contribution to the development of Pancasila and Civic Education learning, namely as a means of shaping and instilling social values that align with educational goals.